Analisis Kausalitas Opini Publik Instagram @Loveable.Redaksi terhadap Pemenuhan Kebutuhan Informasi Seputar Buku Fiksi Remaja - Latasha Latasha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research is to find out the causality analysis of Instagram @loveable.redaksi public opinion on fulfilling the need for information about youth fiction books. The researcher used a quantitative research methodology by distributing questionnaires online via the Google Form which were then distributed to 115 respondents via WhatsApp, LINE, and Direct Message Instagram. The results of this study are based on the results of hypothesis testing using the T & F test, the result is that there is causality of Instagram @loveable.redaksi public opinion towards fulfilling the information needs of youth fiction books. This is proven in the results of the t-test calculation, showing a significance value for the public opinion variable @loveable.redaks on Instagram is 0.000. The value of 0.000 is smaller than the value of 0.05. The conclusion of the study shows that public opinion on Instagram @loveable.redaksi has a positive effect on fulfilling the information needs about fiction books, meaning that the higher the public opinion @loveable.redaks, the fulfillment of the information needs of followers will increase. Keywords: @loveable.redaksi, Government, Instagram, Society, Social Media,